Les noms de tranchées et de boyaux de la Grande Guerre en Champagne - Alain Devos; Pierre Taborelli; Robin Perarnau (EchoGéo)
The toponymy of battlefield and more particularly the trench names of the Great War remains little known without spatial analysis or statistics. The study of trench maps reveals the western front is made of a dense and complex defense network structured according to the geomorphological conditions. To improve the operational aspect of trench maps, the soldiers increased the names, designations and numbers associated with nameboards. The typological study of the 2,500 trench names of Champagne, on 13,000 km of linear for 115 km of front, and their spatial organization from a database under GIS, allows us to better understand the naming logic of these places. Their astonishing diversity and their conventional random designation actually hide a spatial organization into groups of fire trench segments and communication trench or "quarters", of regimental and non-divisional origin. This organisation around cultural themes guarantees the movement of troops and liaison officers in the defense network. The toponyms and trench names constitute a socio-cultural representation of the front area and are today part of the memorial and collective heritage of societies. Trench names raise a lot of scientific questions (authorship, origin of designations, scalar and temporal permanence) and deserve a spatial analysis of the entire western front area.